2017
DOI: 10.1039/c7tc01455d
|View full text |Cite
|
Sign up to set email alerts
|

Relating polymer chemical structure to the stability of polymer:fullerene solar cells

Abstract: This work shows the key role played by the chemical structure of polymers in the UV-degradation of solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 54 publications
4
67
0
Order By: Relevance
“…These figures show the comparative PCE decays for the best performing devices while Figure S3, Supporting Information displays the comparative average trend in PCE decays, for all seven PFSCs. The trends are similar in both 1D and 2D PFSCs, however, it is more pronounced in the 2D PFSCs, certainly due to the effect of the alkylthienyl substituent on the BDT, which were previously shown [33,37] through 1 HNMR of the monomers to make them much less stable.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…These figures show the comparative PCE decays for the best performing devices while Figure S3, Supporting Information displays the comparative average trend in PCE decays, for all seven PFSCs. The trends are similar in both 1D and 2D PFSCs, however, it is more pronounced in the 2D PFSCs, certainly due to the effect of the alkylthienyl substituent on the BDT, which were previously shown [33,37] through 1 HNMR of the monomers to make them much less stable.…”
Section: Resultsmentioning
confidence: 62%
“…From previous studies and as shown in Figure S2, Supporting Information, there are neither changes in blend film morphologies upon exposure nor changes in blend film absorbance before and after UV‐exposure, so these changes can emphatically be attributed to these subtle changes in the TT‐units of the PBDT‐TT polymers. A quick look at the decay of the other J–V parameters of the best performing devices in Figure S4, Supporting Information, reveals that in all considered polymers, loss in J sc is largely the main factor contributing to the PCE decay except for the fluorinated‐TT‐units polymer PBDTTT‐CF (1D) and PTB7‐Th (2D) cells which also record losses in FF.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Unfortunately, it has been shown that many of the highperformance donor polymers suffer from signicant degradation under illumination in ambient conditions. [63][64][65] Photooxidation and degradation of the polymer backbone is one factor that contributes to this instability, most notably in the case of BDT-TT polymers, [66][67][68] and it has been shown to be accelerated by the use of high-boiling point solvent additives such as 1,8diiodooctane in deposition of the active layers. [69][70][71] Another source of instability for OPV devices is related to the electrode or interfacial materials, for example in the use of easily oxidised, low-workfunction metal electrodes 72 or the acidic, hygroscopic poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) hole transport layer, as discussed above.…”
Section: Low-bandgap Donor Polymersmentioning
confidence: 99%